Efisiensi Operasional Perusahaan Properti Indonesia: Peran Likuiditas dan Struktur Modal - Muhammad Ramadhani Kesuma; Aini, Rohana Nur; Irianto, Ellen D. Oktanti; Widaryo, Chandika Mahendra (Yayasan Literasi Sains Indonesia, 2025)
This study aims to examine the impact of liquidity and capital structure on the operational efficiency of property and real estate companies in Indonesia from 2019 to 2023, amidst economic challenges posed by the pandemic. A quantitative approach was employed, utilizing panel data from annual financial reports of companies listed on the Indonesia Stock Exchange, analyzed through random-effects panel regression to assess variable relationships. The findings reveal that liquidity, measured by cash, current, and quick ratios, and capital structure, measured by the debt-to-equity ratio, do not significantly influence operational efficiency, measured by earnings before interest and taxes. This outcome may be attributed to heterogeneity among companies and the pandemic’s disruption of cash flows. Nevertheless, companies with adequate liquidity demonstrated greater resilience during the crisis. The study concludes that optimal liquidity and capital structure management remain crucial for supporting operational efficiency, recommending diversification of funding sources and adoption of digital technologies to enhance competitiveness in the dynamic property market.